Trends of and Prospects for the Development of Fiber-Optic Communication Systems - Konyshev, V. A.; Leonov, A. V.; Nanii, O. E.; Starykh, D. D.; Treshchikov, V. N.; Ubaidullaev, R. R. (Bulletin of the Lebedev Physics Institute, 2023)
— We consider technologies that allow the throughput of fiber-optic transmission systems (FOTSs) to be increased. The need for this is due to a growth in the volume of newly available information, virtualization of network applications, development of cloud services, and consolidation and construction of new data centers. Dense wavelength division multiplexing (DWDM) and introduction of coherent detection with digital signal processing have made it possible to most significantly increase the FOTS capacity. The main directions of FOTS development are the improvement of active equipment and optical fiber lines. This paper is devoted to the trends in the development of active FOTS equipment.